2019
DOI: 10.1111/jvim.15657
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a flash glucose monitoring system in dogs with diabetic ketoacidosis

Abstract: Background: A factory-calibrated flash glucose monitoring system (FGMS; FreeStyle Libre) recently was evaluated in dogs with uncomplicated diabetes mellitus. It is not known if this system is reliable during diabetic ketoacidosis (DKA). Objectives: To assess the performance of the FGMS in dogs with DKA and to determine the effect of severity of ketosis and acidosis, lactate concentration, body condition score (BCS), and time wearing the sensor on the accuracy of the device. Animals: Fourteen client-owned dogs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 43 publications
7
55
3
Order By: Relevance
“…The fact that one dog developed transient Horner syndrome shortly after sensor placement by the pet owner at home suggests, that this procedure, although minimally invasive, should be restricted to veterinarians or well-trained clients. It also supports a more dorsal positioning of the sensor when attached at the neck as demonstrated in the 2 validation studies [5] [12]. Alternatively, a case series suggested that implantation at the waist or back might be advantageous in dogs with less than 10 kg [13].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The fact that one dog developed transient Horner syndrome shortly after sensor placement by the pet owner at home suggests, that this procedure, although minimally invasive, should be restricted to veterinarians or well-trained clients. It also supports a more dorsal positioning of the sensor when attached at the neck as demonstrated in the 2 validation studies [5] [12]. Alternatively, a case series suggested that implantation at the waist or back might be advantageous in dogs with less than 10 kg [13].…”
Section: Discussionmentioning
confidence: 55%
“…Although 42 % of our patients weighed less than 10 kg, we did not observe problems with sensor positioning at the side of the neck in any of these dogs. Nevertheless, dorsal placement as suggested in the 2 validation studies [5] [12] would have been problematic in the smallest dog, a Miniature Pinscher weighing 3.4 kg.…”
Section: Discussionmentioning
confidence: 99%
“…In all dogs, the skin reaction was self-limiting without the need for any medication. In dogs, the development of a mild erythema at the site of the sensor application has been reported in 50% of dogs [ 1 ] and in 7% of dogs [ 2 ]. In humans, skin reactions to the FGMS have been described in several reports [ 40 , 41 , 42 , 43 , 44 ] and can be irritative or allergic skin lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The flash glucose monitoring system (FGMS) is a novel continuous glucose monitoring system (CGMS) recently validated for use in dogs with diabetes mellitus and diabetic ketoacidosis [ 1 , 2 ]. It consists of a 35 mm × 5 mm round sensor, which continuously measures the glucose in the interstitial fluid through a small filament inserted under the skin, allowing more rapid glucose monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…After gathering the data from an at-home glucose curve, the client can schedule a virtual visit with the veterinarian and adjustments in the treatment plan can be made as needed. There are studies that have shown the accuracy of the FreeStyle Libre compared to glucose curves, and the clinical accuracy makes continuous glucose monitoring an attractive alternative for pet owners (Corradini et al, 2016;and Malerba et al, 2020).…”
Section: Mhealth Wearables Smartphone Applicationsmentioning
confidence: 99%